Common parlance English in an Indian medical undergraduate institution: current scenario and ranking the improvement - Pathak, Rakesh Ranjan (International Journal of Research in Medical Sciences, 2025)
Background: Indian undergraduate medical students fail to differentiate word-inflexions, or look-alike-sound-alike words, and words which are not candid contextually. Baseline English vocabulary assessment followed by a gap analysis and training can motivate an improvement. Methods: Harrison’s Textbook of Internal Medicine was the reference textbook for vocabulary. All the asked words in MCQ.1 (pre-test) or MCQ.2 (post-test) were ensured in Oxford English Mini Dictionary to verify their common parlance use. Dorland’s Illustrated Medical Dictionary was referred to verify semantic similarity. The chosen words’ usage frequency rank was decided as per COCA corpus. After 7 months, MCQ.2, with word-to-word match of nearly 5000 higher rank (hinted as per internal assessment), was held and students were expected to repeat a similar performance. Results: In MCQ.1, 89 students got enrolled and 87 participated. In MCQ.2, 104 students were enrolled and 103 participated (an indicator of motivation). On 2-tailed paired t-test, p value was 0.1129, confidence interval at 95% significance was -0.54 to +0.06 and t-value was 1.6017 (MCQ.1 and MCQ.2 performances were essentially similar). Conclusions: Similar performance at higher rank indicates that the training uplifted the students’ vocabulary by at least 5000 ranks within 7 months.